Molecular classification of endometrial cancers translated into practice - Presl, Jiří; Vaněček, Tomáš; Michal, Michael; Bouda, Jiří; Kosťun, Jan; Vlasák, Pavel; Stráník, Petr (Ceska gynekologie, 2021)
OBJECTIVE: The main objective of the article is to clearly inform healthcare professionals about the newly implemented molecular classification of endometrial cancer into practice. METHODS: Summary of current knowledge, recommendations and new procedures relating to molecular genetic examination of the tissues of patients with endometrial carcinoma. RESULTS: Endometrial cancer is currently dia-gnosed on the base of histopathological morphology. According to the classical Bokhman division, we distinguish between two relatively wide groups of tumors which are different in pathogenesis: type I - estrogen-dependent tumors, clinically usually indolent, and type II - non-endometroid tumors, clinically aggressive, without dependence on estrogen stimulation. This classification fulfills a didactic purpose and provides easy orientation for epidemiological data, but is not suitable for stratification due to the overlap of clinical, pathological and molecular features. The Cancer Genome Atlas project classifies endometrial tumors into 4 groups based on molecular genetic features. CONCLUSION: Integration of the histopathological findings along with molecular classification appears to be the best approach for evaluating each individual tumor. This will help to achieve the ideal stratification of patients for treatment regimens.
Keywords: Female; mutace; Carcinoma, Endometrioid; nádory endometria; TP53 mutation; Endometrial Neoplasms; POLE mutation –mismatch repair-deficient tumors; endometrial (endometrioid) carcinoma; endometroidní karcinom; ženské pohlaví; Humans; Mutation; lidé; non-specific molecular profile; Endometrial carcinoma; The Cancer Genome Atlas project; molecular classification